4107 Limited Echocardiogram Examinations Performed by Intensivists: A Surgeon-Driven Multidisciplinary Program. Issue 1 (January 2017) - Ferrada, Paula; Evans, David; Parker, Sara; Pedram, Sammy; Sessler, Curtis N.
Limited transthoracic echocardiogram (LTTE) has been introduced as a tool to direct resuscitation. At our institution, a multidisciplinary training program was instituted. Our hypothesis is that in spite all efforts for multidisciplinary training, certification, and credentialing, limited echocardiograms are under billed for. A training program was implemented in August 2010. This was followed by a process of credentialing and adding LTTE to the billing privileges for providers. Institutional Review Board approval was obtained to review all the studies performed from August 2010 to October 2014. About 4107 LTTEs were performed during the study period. Only 685 examinations were billed for (16.6%). The total amount billed for all the studies was $80, 819.00. The number of studies billed for and performed in the emergency department (ED) were 342, and 343 studies were billed while performed in the intensive care unit (ICU). Our institution received payment at a higher rate when the studies were performed in the ICU (71.7%) versus ED (49.4%), P < 0.0001. The total actual reimbursement for the ED was $6487.29 and for the ICU was $8213.95 for a total of $14, 701.24. The mean reimbursement amount was $35.59. If all of the studies were billed for and reimbursed at the average payment amount, the institution would have received $146, 168.13. A multidisciplinary approach is pivotal for the success of intensivist-driven bedside echocardiogram programs. Education regarding credentialing and billing is a necessary addition to ensure sustainability of such efforts.